O Centro de Estudos Latino-Americanos da Universidade de Varsóvia e sua importância para o tema da integração na América Latina - Kuczkowski, Claudio (2007)
The Center of Latin-American Studies of the University of Warsaw and its importance for the theme of the integration in Latin America are demonstrated starting from two different points of view: first, for the present time of the discussions around the integration and, second, for the need of organisms producing of scientific information about the relationship processes and Latin-American integration. Starting from that, the analysis agreed the Latin-American integration describing and characterizing the process. In the second moment, it is studied the institutional process of the Academic Centers of Research, analyzing the transformations, directions and general perspectives. After, it turn about the constitution of a concept of Latin-Americanism, the understanding of the adopted roads (orientations and thematic options) for the reach of the objectives projected in each academically space. Finally, the relationship is approached between CESLA and the Latin-American integration, reminding the conditions of creation of the Center and the social functions of the University, to which is linked. The methodology is used of primary sources, such as the creation documents and operation of CESLA and the existent agreements between this and the several Latin-American research centers, supporting this research. At the same time, the secondary sources, also of great relevance, they are the Polish bibliographical production and Latin-American on the main object of the research and interviews with government authorities and/or intellectuals of the two areas, as foundation that the different social agents posture on the theme is historical source of solid relevance. To conclude, it is assumed that an unanimous posture no exists in CESLA about the relationships and the Latin-American integration, including own intellectuals in Latin America. The variety of centers and objectives, the economical and political subjects around the creation and maintenance of the centers, the external influences in the result, the non use of the researches and the preexistence of some facilitators for the initiation of the centers do each one possesses unique characteristics, own to a specific reality, without losing the contact with the general context. In this context, CESLA appears as connection mechanism between the production and the use of the scientific knowledge, presenting possible sceneries, forming attitude and introducing a perspective of universalization of the knowledge, vectors capable to explain the current mentality exchanges.